A Critical Discourse Analysis of Gender Equity and Sex Education in Indonesian High School Biology Textbooks - Holy Ichda Wahyuni; Radius Setiyawan; Agus Budiman; Nadia Shoukat (Universitas Pendidikan Ganesha, 2025)
Biology learning materials, particularly on the reproductive system, often emphasize mechanistic and biological aspects while overlooking the importance of integrating adolescent sex education and gender equity values. This gap may perpetuate misconceptions and gender bias among students. This study aims to critically analyze the representation of gender equity and sexuality education in senior high school Biology textbooks through a critical discourse analysis framework. A qualitative research design was employed, utilizing Norman Fairclough’s three-dimensional model consisting of text analysis, discourse practice analysis, and social practice analysis. The study involved three widely used Grade XI Biology textbooks, including one government-issued and two private publishers' editions as comparative data sources. The findings reveal a uniform pattern of placing reproductive system topics at the end of the textbooks, predominantly presenting anatomical and physiological content without integrating comprehensive, inclusive, and gender-equitable sexuality education. Moreover, the textbooks demonstrate gender bias, insufficient discussions on consent, sexual violence, and unequal access to contraceptive information. This study concludes that the textbooks reproduce patriarchal ideologies and exclusive scientific discourse, failing to address adolescents' psychosocial and ethical aspects of sexuality. The findings highlight the urgent need for textbook revisions that promote comprehensive, gender-equitable, and contextually relevant sex education for high school students.